2012
DOI: 10.1177/1534735412458828
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Product of Soybean, Black Bean, and Green Bean Mixture Induces Apoptosis in a Wide Variety of Cancer Cells

Abstract: Previous studies have shown that soybean fermentation products can act as cancer chemoprevention or therapeutic agents. In this study, the anticancer activities of a fermentation product of soybean, black bean, and green bean mixture (BN999) were investigated. We found that BN999 inhibited the growth of human breast cancer AU565 cells and prostate adenocarcinoma PC-3 cells but not that of normal human cells. BN999 induced apoptosis in various human cancer cells but not in normal human cells. BN999 treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Chia et al was the first to claim the cytotoxic properties of fermented bean mixture (BN999) containing MB ( Vigna radiata ), SB ( Glycine max ) and black SB ( Glycine max ) against breast (AU565) and prostate (PC3) cancer cells. In their study, the fermentation product was found to selectively inhibit cancer cell proliferation and induced cell death . In addition, fermented common bean ( Phaseolus vulgaris L.) were reported to induced apoptosis and G1 to S phase cell cycle arrest on human colon cancer cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chia et al was the first to claim the cytotoxic properties of fermented bean mixture (BN999) containing MB ( Vigna radiata ), SB ( Glycine max ) and black SB ( Glycine max ) against breast (AU565) and prostate (PC3) cancer cells. In their study, the fermentation product was found to selectively inhibit cancer cell proliferation and induced cell death . In addition, fermented common bean ( Phaseolus vulgaris L.) were reported to induced apoptosis and G1 to S phase cell cycle arrest on human colon cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the fermentation product was found to selectively inhibit cancer cell proliferation and induced cell death. 45 In addition, fermented common bean (Phaseolus vulgaris L.) were reported to induced apoptosis and G1 to S phase cell cycle arrest on human colon cancer cells. 46 More specifically, our results have demonstrated that FMB possessed greater apoptosis inducing wileyonlinelibrary.com/jsfa effect against breast cancer cells than FSB.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin-rich BSB seed coat extract possibly reduces the development of tumors in various organs such as intestines [51], breast [109], prostate [65,110], stomach [80], ovary [111], endometrium [112], and liver [113]. In addition to the anthocyanins, saponins also prevent cancer cells from proliferation and spreading throughout the body [114].…”
Section: Health Benefits Of Anthocyanins Rich Bsbmentioning
confidence: 99%
“…Mung bean seeds and sprouts have been recorded to have in vitro cytotoxic and immunomodulatory effects and germination was found to significantly improve the bioactivities of mung bean seeds [6, 18]. On the other hand, fermented legume products that contain mung bean as one of the major ingredients have recorded inhibitory effects on the growth of mouse colon cancer xenograft without any side effects [8]. To date, chemopreventive effects on breast cancer solely contributed by fermented mung bean have yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mung bean sprouts extract also induced cell cycle arrest and apoptosis on the tested cancer cells [6]. Besides germination, products that contained enzyme hydrolysed [7] or fermented [8] mung bean have also been identified as potential cancer chemopreventive or therapeutic agents. We have previously reported that fermentation can significantly improve GABA content of mung bean [9].…”
Section: Introductionmentioning
confidence: 99%